An investigation of Business Process maturity: a case study in a South African parastatal - Nteo, Maleho (Department of Mechanical Engineering, 2018)
Business Process Management (BPM) has become one of the management approaches adopted by many organisations that strive to survive in a turbulent and competitive environment. BPM offers the means to manage and optimize business processes with the objective of improved efficiency and effectiveness; thereby improving the potential of business success. However, the extent to which BPM influences business success is a matter of debate with diverse schools of thought finding it difficult to reach consensus regarding the critical success factors of BPM and the extent at which processes and people influence business success. The capability of an organisation or enterprise is the ability to deliver on a desired outcome. In this dissertation, the enterprise capabilities of BPM are investigated. The research sets out to investigate the BPM maturity level of a South African parastatal. The intention is to identify and improve on those factors that influence maturity of the enterprise capabilities and may have negative impact on stakeholders. The approach taken to address the research objectives drew on case study methodology. Fieldwork was conducted using company documents, observation, a questionnaire and in-depth interviews. The questionnaire responses were qualitatively analysed using the categories of Hammer's model of enterprise capability. The research findings identified weaknesses in all categories of enterprise capability though expertise appeared to be thriving. The findings further suggest that weaknesses in leadership and the leadership style in particular impact on the effectiveness of business processes. The leadership style was seen as the major driver to impede process effectiveness. The following themes describing leadership style were derived from interviews: creation of sense of belonging, degree of approachability and extent of collaboration. In order to improve the BPM in the case company, the following recommendations were made: communication sessions, awareness training and process remodelling. The research study also provides the opportunity to understand BPM in a broader context, thus having potential for transferability to other organisations.